Peculiarities of the Dependence of the Strain Coefficient on the Deformation of Metal Films - K.V. Tyschenko; L.V. Odnodvorets; C.J. Panchal; I.Yu. Protsenko (Журнал нано- та електронної фізики)
We propose a phenomenological theory to explain the physical nature of the maximum or minimum in the dependence of the instantaneous longitudinal strain coefficient, γli, versus the strain, εl, in double-layer films Fe/Cr, Cu/Cr and Fe/a-Gd. The theory is based on the analysis of extremum (maximum or minimum), which is obtained by simplifying the equation ∂γli/∂εl = 0. It is concluded that the appearance of a maximum or minimum is caused by both non-linear deformation processes in εl and possible structural changes in the films.